Poly(ε‐caprolactone) and Poly(ω‐pentadecalactone)‐Based Networks with Two‐Way Shape‐Memory Effect through [2+2] Cycloaddition Reactions. Issue 4 (19th December 2017) - Pilate, Florence; Stoclet, Gregory; Mincheva, Rosica; Dubois, Philippe; Raquez, Jean‐Marie
Abstract: In this work, the synthesis and characterization of triple‐shape and two‐way shape‐memory effect of novel poly(ester‐urethane)s (PURs) made of a poly(ε‐caprolactone) (PCL) and poly(ω‐pentadecalactone) (PPDL) segments and N, N ‐bis(2‐hydroxyethyl)cinnamide (BHECA) monomer by reactive extrusion (REx) is reported. PCL and PPDL are chosen as semicrystalline segments because of their inherent ability to undergo tensile elongation upon cooling, as prerequisite for the two‐way shape‐memory effect. BHECA is used as the "cross‐linker" due to its ability to participate in reversible [2+2] cycloaddition reaction and to mainly maintain the crystalline features of semicrystalline precursors within these PURs. This novel simple strategy is considered extremely versatile and adaptive because of the possibility to vary crystallizable segments and coupling agents, thus paving the way to the design of a multitude of triple (or more) shape‐memory polymers with two‐way behavior. Feasibility with PURs containing PCL, PPDL, and BHECA is demonstrated by adjusting the shape‐memory behavior (one and two‐way effects), and studying the structure–property relationships of the resulting PURs by DSC, DMTA, and 2D wide angle X‐ray scattering analyses while varying the weight composition of the two semicrystalline segments. Abstract : Two‐way shape changes into photo‐crosslinked semicrystalline poly(ester‐urethane)s made of α, ω‐diol poly(ε‐caprolactone) and poly(ω‐pentadecalactone) segments are observed. Due to the efficiency in the maintenance of precursor crystallinity properties, crystallization‐induced elongation and melting‐induced contraction phenomena can be detected into resulting poly(ester‐urethane)s, depending on the weight composition of the two semicrystalline segments.